2021
DOI: 10.1093/cid/ciaa1857
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Pump Inhibitor Use and the Risk of Community-Associated Clostridium difficile Infection

Abstract: Background Proton-pump inhibitors (PPIs) have been reported to increase the risk of community-associated Clostridium difficile infection (CDI), but the association remains disputed. Methods A nationwide cohort study among adults in Denmark, 2010–2013, linking register data on C. difficile testing, filled prescriptions, and patient characteristics. All incident episodes of community-associated CDI (ie, positive culture, molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 32 publications
1
26
1
2
Order By: Relevance
“…Our study reported a significant association between the onset of CDI and PPI use, according to the existing literature ( 13 , 14 ). How PPI administration increases the risk of CDI is unclear.…”
Section: Discussionsupporting
confidence: 82%
“…Our study reported a significant association between the onset of CDI and PPI use, according to the existing literature ( 13 , 14 ). How PPI administration increases the risk of CDI is unclear.…”
Section: Discussionsupporting
confidence: 82%
“…With respect to PPIs, which are widely prescribed in Spain [34], they were classified as PIMs in 167 patients. PPIs may be related to adverse outcomes, such as fractures [35], hypomagnesaemia [36][37][38][39], recurrent C. difficile infection [40,41], dementia [42,43], communityacquired pneumonia [44], or severe COVID-19 infection [45][46][47]. Remarkably, in 160 (95.8%) patients, PPI prescription was assigned to implicit STOPP criterion A1.…”
Section: Discussionmentioning
confidence: 99%
“…The Updated Charlson Comorbidity Index [22] was calculated, adjusted by age and categorized by tertiles (2-6, 7-8 and 9-14). Barthel Index was categorized as independency (100 points), minimal dependency (60-95), moderate dependency (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55), severe dependency (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and complete dependency (<20) [23]. Some chronic conditions were grouped according to clinical criteria, as in Baré et.al.…”
Section: Sampling and Analysismentioning
confidence: 99%
“…As can be seen in Table 1 [ 3 , 4 , 9 , 10 , 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], the danger in recent public health failures is not simply that time and money was expended in unsuccessfully combatting the NCD epidemic. It is that some of the recommendations actually further erode both the microbiome and human health.…”
Section: The Updated Science–application Gap: Ancient Personal Responsibility Solutions To Stop Ncdsmentioning
confidence: 99%